PENERAPAN METODE GALLERY WALK TERHADAP MINAT DAN HASIL BELAJAR IPAS KELAS V SD NEGERI 39 BONTONYELENG - Nurul Ismi; Amri Amal; Nurfadilah (STKIP Subang, 2026)
This study aimed to describe the implementation of the Gallery Walk method and to analyze its effect on improving students’ interest and learning outcomes in IPAS among fifth-grade students of SD Negeri 39 Bontonyeleng. The research employed a quantitative approach using a pre-experimental design with a one-group pretest–posttest model. The sample consisted of 26 fifth-grade students. The research instruments included a learning interest questionnaire and an IPAS achievement test. Data were analyzed using descriptive statistics and N-gain analysis.The results showed that students’ learning interest increased from an average score of 42% before the implementation of the method to 69% after the implementation, indicating an increase of 27 percentage points. In addition, students’ IPAS learning outcomes also improved, as indicated by N-gain values ranging from 0.5 to 1.00 with an average of 0.7, which falls into the moderate category. These findings indicate that the Gallery Walk method is effective in enhancing both learning interest and IPAS learning outcomes of fifth-grade students at SD Negeri 39 Bontonyeleng.